225k views
4 votes
Please help! I have very limited time to answer, but I am really stumped!

Please help! I have very limited time to answer, but I am really stumped!-example-1

1 Answer

3 votes

Answer:

A

Explanation:

So we have the function:


f(x)=y=\sqrt[3]{x-2}+8

To find the inverse of the function, we can flip x and y and then solve for y. Therefore:


x=\sqrt[3]{y-2}+8

Solve for y to find our inverse.

Subtract 8 from both sides:


x-8=\sqrt[3]{y-2}

Cube each side. The right cancels:


(x-8)^3=y-2

Add 2 to both sides:


y=(x-8)^3+2

Therefore, our inverse is:


f^(-1)(x)=(x-8)^3+2

The answer is A

User Kirill Shlenskiy
by
5.9k points